2013
DOI: 10.1371/journal.pone.0054410
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Dlgh-1 in Planar Cell Polarity and Skeletogenesis during Vertebrate Development

Abstract: The development of specialized organs is tightly linked to the regulation of cell growth, orientation, migration and adhesion during embryogenesis. In addition, the directed movements of cells and their orientation within the plane of a tissue, termed planar cell polarity (PCP), appear to be crucial for the proper formation of the body plan. In Drosophila embryogenesis, Discs large (dlg) plays a critical role in apical-basal cell polarity, cell adhesion and cell proliferation. Craniofacial defects in mice carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 80 publications
(128 reference statements)
1
23
0
Order By: Relevance
“…[26][27][28] It has been shown that the loss of Dlg1 may affect craniofacial development through the disruption of WNT/planar cell polarity (PCP) signalling, which is involved in the process of dynamic tissue movement during organogenesis known as convergent extension. 28,29 It is worth noting that another important regulator of Wnt/PCP signalling is Wnt5a, which deficiency in mice leads to complete clefting of the secondary palate due to inhibition of the directional migration of cells required for palate formation. 30,31 Interstitial deletions of 3q29 in humans have recently been described as a new microdeletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] It has been shown that the loss of Dlg1 may affect craniofacial development through the disruption of WNT/planar cell polarity (PCP) signalling, which is involved in the process of dynamic tissue movement during organogenesis known as convergent extension. 28,29 It is worth noting that another important regulator of Wnt/PCP signalling is Wnt5a, which deficiency in mice leads to complete clefting of the secondary palate due to inhibition of the directional migration of cells required for palate formation. 30,31 Interstitial deletions of 3q29 in humans have recently been described as a new microdeletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other family members, Dlg1 (SAP97) mutant mice are neonatal lethal, displaying craniofacial defects and kidney, urogenital, and lens development defects (Caruana and Bernstein 2001;Naim et al 2005;Mahoney et al 2006;Iizuka-Kogo et al 2007;Rivera et al 2009). More recently, Dlg1 null mice were shown to also display defects in skeletogenesis of the trunk and limb structures and, importantly, similarly to loss of Scribble, defects in neural tube, eyelid closure, and in the disorganization of the stereociliary bundles in the cochlea (Rivera et al 2013). These studies indicate a novel role for Dlg1 in PCP signaling.…”
Section: Mus Musculusmentioning
confidence: 90%
“…In Drosophila, Scribble physically and genetically interacts with Vangl2 to direct PCP processes in the eye and the wing , and similar interactions have been found between Scribble and Vangl2 in zebrafish in the control of the PCP-mediated convergence extension movements during gastrulation (Wada et al 2005). Recent analysis of Dlg1 and Dlg3 knockout mice has also implicated mammalian Dlg in planar cell polarity regulation with both of these mice displaying at low penetrance the PCP mutant phenotypes, namely, cochlear hair cell misorientation and neural tube closure defects (Rivera et al 2013;Van Campenhout et al 2011). Finally, Lgl can bind to the PCP protein Dsh, which regulates Lgl localization, in both Drosophila epithelium and Xenopus tissues (Dollar et al 2005).…”
Section: Planar Cell Polaritymentioning
confidence: 68%
“…In contrast to other family members, Dlg1 (SAP97) mutant mice are neonatal lethal, displaying craniofacial defects and kidney, urogenital, and lens development defects (Caruana and Bernstein 2001;Naim et al 2005;Mahoney et al 2006;Iizuka-Kogo et al 2007;Rivera et al 2009). More recently, Dlg1 null mice were shown to also display defects in skeletogenesis of the trunk and limb structures and, importantly, similarly to loss of Scribble, defects in neural tube, eyelid closure, and in the disorganization of the stereociliary bundles in the cochlea (Rivera et al 2013). These studies indicate a novel role for Dlg1 in PCP signaling.…”
Section: Mus Musculusmentioning
confidence: 90%